2014
DOI: 10.1039/c3py01572f
|View full text |Cite
|
Sign up to set email alerts
|

Reduction-sensitive functionalized copolyurethanes for biomedical applications

Abstract: In the present paper we combine functionalization and biodegradation in the rational design of polymers that can be used as carrier systems for drug delivery in the colon. Functionalization of new polyurethanes (PUs) was achieved by thiol–ene coupling reactions, a simple and straightforward procedure included among the so-called click reactions, which are currently accepted as one of the most powerful tools in organic chemistry. Enhancement of the degradability of the new materials by the introduction of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
28
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 36 publications
3
28
0
Order By: Relevance
“…The degradation under nitrogen atmosphere proceeded in one stage, with a maximum associated weight loss at temperatures ranging from 282°C to 300°C, and an observed weight loss of above 89%. These values follow a general trend observed in other synthetic polyurethanes and the weight loss could reach 100 wt % when an oxidative atmosphere is used.…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…The degradation under nitrogen atmosphere proceeded in one stage, with a maximum associated weight loss at temperatures ranging from 282°C to 300°C, and an observed weight loss of above 89%. These values follow a general trend observed in other synthetic polyurethanes and the weight loss could reach 100 wt % when an oxidative atmosphere is used.…”
Section: Resultssupporting
confidence: 84%
“…This method is based on glutathione‐mediated lysis under physiological conditions of disulfide bonds incorporated into the polymer skeleton. The general validity of this strategy has been supported by previously published works related with various HMDI‐ and MDI‐PUs …”
Section: Introductionmentioning
confidence: 56%
“…Very recently, l ‐cystine diamine was polymerized with fatty dicarboxylic acids in solution polycondensation route to make poly(disulfide amide) nanoparticles for docetaxel delivery . These amino acid‐based poly(disulfide)s were used as nanoscaffolds for delivering anticancer drugs and gene . These examples clearly envisage the importance of the disulfide polymers as reduction degradable thermoplastics and also as useful scaffold material for biomedical applications.…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8] PUs exhibit excellent physical properties and biocompatibility and have been widely used in biomedical implants. 21 The work from different research groups has revealed that reduction-sensitive shell-sheddable micelles, [22][23][24][25][26][27] main chain degradable nanoparticles [28][29][30][31][32] and reversibly crosslinked polymeric nanocarriers [33][34][35][36] display significantly improved in vitro and in vivo anticancer efficacy as compared to the non-sensitive counterparts. [12][13][14][15][16] It is found that drug release from common biodegradable polymeric nanoparticles is generally slow and incomplete, leading to compromised therapeutic efficacy in vitro and in vivo.…”
mentioning
confidence: 99%